Blockade of dopamine D1‐like receptor signalling protects mice against OVA‐induced acute asthma by inhibiting B‐cell activating transcription factor signalling and Th17 function. (25th October 2013) - Gong, Subo; Li, Jinxiu; Ma, Libing; Li, Keng; Zhang, Li; Wang, Guyi; Liu, Yi; Ji, Xiaoying; Liu, Xiaokun; Chen, Ping; Ouyang, Ruoyun; Zhang, Shu; et al.
<x xml:space="preserve">Abstract</x> Previous studies have consistently demonstrated that dopamine D1‐like receptor (D1‐like‐R) signalling is implicated in the pathogenesis of experimental autoimmune encephalomyelitis and type I diabetes. Given that allergic asthma shares certain disease aetiology similarities with autoimmune diseases, we conducted studies in OVA‐induced mice aiming to address the impact of D1‐like‐R signalling on the pathogenesis of allergic asthma. It was noted that blockade of D1‐like‐R signalling provided protection for mice against OVA‐induced acute asthma. Particularly, treatment of OVA‐induced mice with SCH23390, a D1‐like‐R antagonist, significantly attenuated inflammatory infiltration in the airways along with repressed goblet cell hyperplasia and mucus production, as well as airway resistance. By contrast, administration of SKF83959, a D1‐like‐R agonist, displayed the opposite effect. Blockade of D1‐like‐R signalling impaired Th17 function, as manifested by a significant reduction of Th17 cells in the spleen and bronchoalveolar lavage fluid. Mechanistic studies revealed that D1‐like‐R signalling enhances B‐cell activating transcription factor activity, which then transcribes the expression of RORγt, a Th17 transcription factor; accordingly, D1‐like‐R signalling regulates Th17 differentiation to promote the development of allergic asthma. Taken together, the data obtained in the present suggest that blockade of D1‐like‐R signalling could be an effective therapeutic strategy for the prevention and treatment of allergic asthma in clinical practice.